Reconocer la diversidad de la museología. Reflexiones a partir del caso español - Fabien Van Geert (Midas: Museus e Estudos Interdisciplinares)
Museology has been defined and theorised in various ways, halfway between theory and practice. After long debates about what has long been seen as a dichotomy between these two perspectives, the growing development of museology in the global context raises new research questions, in particular whether it is appropriate to speak of museology in the singular or museologies in the plural. This question forms the argumentative basis of this article, based on the example of museology in Spain. The methodology adopted includes literature review and is based also on my empirical knowledge on the subject matter. After attempting to define some of specificities of the Spanish case, this study contributed to reflect on new theoretical fields that recognise the existence of different museologies in the world, brought into dialogue on the basis of a comparative and geopolitical approach to museology. We conclude that these two approaches enable us to gain a better understanding of museology, in its interrelation between theoretical and practical aspects. To do this, it is important to recognise and understand the different museologies, and the ways in which their interweaving contributes to shaping museology. Thus, analysing local contexts of production is fundamental, and should be the starting point for museology as a multi-disciplinary area of research. This theoretical and methodological stance would enable the conception of a more inclusive approach to museology, recognising and valuing the diversity that exists within it, whether they come from Spain, France or elsewhere in the world.